Ausgaben- und Preiselastizitäten der Nahrungsmittelnachfrage auf Basis von Querschnittsdaten: Eine Systemschätzung für die Bundesrepublik Deutschland; Estimating expenditure and price elasticities of food commodities using German cross-sectional household data - Silke Thiele (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– This study presents a procedure to estimate expenditure and price elasticities of food commodities from cross-sectional data. There are two problems with the use of cross-sectional data: First, price-information is not sufficient in these data. To derive "adjusted prices" from cross-sectional data an approach of COX and WOHLGENANT is applied. Second, zero expenditures for some commodity groups can be observed. To avoid selectivity bias a generalization of the HECKMAN procedure is employed. Both, the adjusted prices and the bias correction are included in a Linear Expenditure System. It can be concluded that expenditure and price elasticities could differ significantly between household characteristics. The research results suggest that attempts to use only the mean elasticity coefficient as a description of consumer behaviour without regarding the variances between households might be not appropriate.
Keywords: 330; Lebensmittelmarkt; Gesamtwirtschaftliche Nachfrage; Elastizität; Deutschland